2017
DOI: 10.1111/nep.12977
|View full text |Cite
|
Sign up to set email alerts
|

Globotriaosylsphingosine induces oxidative DNA damage in cultured kidney cells

Abstract: Fabry disease (FD) is a lysosomal disorder caused by mutations leading to a deficient activity α-galactosidase A with progressive and systemic accumulation of its substrates. Substrates deposition is related to tissue damage in FD, but the underlying molecular mechanisms remain not completely understood. DNA damage has been associated with disease progression in chronic diseases and was recently described in high levels in Fabry patients. Once renal complications are major morbidity causes in FD, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…36,38 Moreover, oxidative damage to DNA and RNA is related to a several number of pathologies 39,40 involving defects in important processes such as transcription and replication, finally resulting in cell death and mutagenesis. In this regard, GA, the major organic acid accumulated in GA-I, increased the DNA DI in peripheral leukocytes in a dose-dependent fashion that was attenuated by L-car treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,38 Moreover, oxidative damage to DNA and RNA is related to a several number of pathologies 39,40 involving defects in important processes such as transcription and replication, finally resulting in cell death and mutagenesis. In this regard, GA, the major organic acid accumulated in GA-I, increased the DNA DI in peripheral leukocytes in a dose-dependent fashion that was attenuated by L-car treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that ROS can attack nuclear and mitochondrial DNA generating oxidized forms, mainly urinary 8-OH-dG, that are continuously repaired, and the injured nucleosides are excreted in the urine. 36,38 Moreover, oxidative damage to DNA and RNA is related to a several number of pathologies 39,40 involving defects in important processes such as transcription and replication, finally resulting in cell death and mutagenesis. 36 As for to the antioxidant defenses, our data demonstrate that GA-I patients have a reduction of urinary antioxidant capacity at diagnosis and that L-car treatment was able to improve the antioxidant status in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of ischemia, these are irreversible situations that will lead to end-stage kidney disease [47][48][49][50][51][52][53]. In this regard, different studies have shown the participation of some mediators involved in such mechanisms in FD [42,43,46,[54][55][56][57]. It is also important to consider especially proteinuria, since it is considered an important variable for the diagnosis and monitoring of patients with Fabry disease.…”
Section: Pathogenesismentioning
confidence: 99%
“…Recent data highlighted the role of oxidative stress in FD pathophysiology. FD patients present high lipid and protein oxidative damage, decreased antioxidant defences and increased inflammatory biomarkers and cytokines [3][4][5][6][7][8][9][10]. Excess intracellular Gb3 induces oxidative stress and up-regulates the expression of cellular adhesion molecules in vascular endothelial cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…Excess intracellular Gb3 induces oxidative stress and up-regulates the expression of cellular adhesion molecules in vascular endothelial cells [5]. Moreover, it has been suggested that pro-oxidant state occurs, is correlated and seems to be induced by Gb3 in Fabry patients [9].…”
Section: Introductionmentioning
confidence: 99%